Family-school-hospital collaboration model for urinary system tumor early screening education - Fen Zhou; Ping Yu; Xiaofen Yu; Xuyan Han; Zheng Wang (Frontiers in Public Health, 2026)
Objective To develop and validate a 3D printing-assisted family-school-hospital collaborative education model for urinary system tumor early screening, and to evaluate its association with changes in medical students’ knowledge and core competencies related to tumor early detection. Methods A non-randomized controlled pre-post study was conducted among 120 clinical medical interns (60 in each group). The intervention group received a 6-month family-school-hospital collaborative program via family WeChat groups, while the control group received traditional clinical teaching only. The primary outcome was knowledge score using questions from the National Medical Licensing Examination. Secondary outcomes included five core competencies: social medical curiosity, self-directed learning ability, doctor-patient communication ability, inter-professional teamwork competence, and transformative learning readiness. Data were analyzed using independent t-tests, change-score analysis. Results After adjusting for baseline, the intervention group showed significantly greater improvements in knowledge score (mean change: 12.48 ± 9.98 vs. 6.28 ± 11.55; p = 0.0046, Cohen’s d = 0.56, 95% CI: 1.97 to 10.43), social medical curiosity (mean change: 1.55 ± 5.26 vs. 1.10 ± 5.02; p = 0.0458, Cohen’s d = 0.37, 95% CI: 0.037 to 3.896), self-directed learning ability ( p = 0.0458, Cohen’s d = 0.38, 95% CI: 0.037 to 3.896), and doctor-patient communication ability ( p = 0.0238, Cohen’s d = 0.39, 95% CI: 0.0494 to 0.6834). Inter-professional teamwork competence and transformative learning readiness showed no significant differences after baseline adjustment (both p > 0.05). Conclusion The 3D printing-assisted family-school-hospital collaborative education model was associated with significant improvements in medical students’ knowledge and core competencies for urinary system tumor early screening. This localized, family-oriented approach provides a feasible and replicable teaching strategy for cancer early detection education, supporting the integration of medical education and public health practice.